Interdisciplinarity and Indigenous Studies: A Māori Perspective. Issue 3 (3rd July 2018) - Lilley, Spencer
ABSTRACT: This paper uses a Māori epistemological approach, to demonstrate why indigenous knowledge systems should be recognised as the ultimate example of interdisciplinary interaction. Over the last 25 years, the library and information professions in New Zealand have become aware of the need to ensure that the full potential of mātauranga Māori is realised. This involves thinking less about 'Māori studies', and being more focused on the interaction and integration of the inter-disciplinary components that constitute the totality of mātauranga Māori. Within this context, library and information management institutions are responsible for ensuring that they are able to provide the resources and services required by Māori wishing to draw on knowledge across disciplines, in ways that may ordinarily be seen as unnatural partners within western academic frameworks. Glossary of Māori words: Aituā (Taiao): Environmental disasters; Atua: Māori gods; Hapū: Sub-tribe; Haumietiketike: God of fern-roots and berries; Hukatai: Sacred stone of knowledge; Io: The supreme being; Io-Matua: Supreme parent; Iwi: Tribe; Kaitiaki: Guardians; Karakia: Incantations; Mātauranga a iwi: Tribal knowledge system; Mātauranga koiora: Biology; Mātauranga Māori: Māori knowledge systems; Mātauranga taupuhi kaiao: Ecology; Papatuanuku: Mother Earth; Ranginui Sky Father; Rehutai: Sacred stone of knowledge; Rongomātane: God of cultivated crops & peace; Ruamoko: God of earthquakes; Tāne: God of forests; Tangaroa: God of the ocean & fish; Tapu: Restricted; Tāwhirimatea: God of the winds; Te Aomārama: World of light; Teina: Mentee; Te Kete Aronui: Basket of everyday knowledge; Te Kete Tuatea: Basket of evil arts and sorcery; Te Kete Tuauri: Basket of ancestral knowledge; Te Kore: Complete darkness; Te Po: Nights; Te reo Māori: Māori language; Tikanga Māori: Māori customs; Tuakana: Mentor; Tūkinotanga ā-taiao: Environmental pollution; Tukutuku: Woven panels; Tūmatauenga: God of war; Waiata: Sung poetry; Whakairo: Carvings; Whakapapa: Genealogy; Whanaketanga: Evolution; Whanau: Extended family; Whare wananga: Sacred schools of learning